2015
DOI: 10.1007/s00401-015-1502-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic traumatic encephalopathy pathology in a neurodegenerative disorders brain bank

Abstract: Chronic traumatic encephalopathy (CTE) is a progressive neurodegenerative disorder linked to repetitive traumatic brain injury (TBI) and characterized by deposition of hyperphosphorylated tau at the depths of sulci. We sought to determine the presence of chronic traumatic encephalopathy (CTE) pathology in a brain bank for neurodegenerative disorders for individuals with and without a history of contact sports participation. Available medical records of 1,721 men were reviewed for evidence of past history of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
211
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(216 citation statements)
references
References 39 publications
5
211
0
Order By: Relevance
“…In 2005, a syndrome of progressive cognitive, motor and neuropsychiatric symptoms initially described almost 80 years prior [1,2] found renewed interest when these symptoms were described in two professional American football players whose brains showed an apparently unique distribution of tau pathology, or neurofibrillary tangles (NFTs) [3,4]. This tauopathy called chronic traumatic encephalopathy (CTE) has since been identified postmortem in a small but growing number of individuals [4][5][6][7], resulting in widespread media attention and public health concern about the possible neurodegenerative effects of TBI. Based on preliminary neuropathological diagnostic published earlier this year [8], CTE has thus far only been found postmortem in individuals who were exposed to repetitive concussive or subconcussive head trauma during life [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005, a syndrome of progressive cognitive, motor and neuropsychiatric symptoms initially described almost 80 years prior [1,2] found renewed interest when these symptoms were described in two professional American football players whose brains showed an apparently unique distribution of tau pathology, or neurofibrillary tangles (NFTs) [3,4]. This tauopathy called chronic traumatic encephalopathy (CTE) has since been identified postmortem in a small but growing number of individuals [4][5][6][7], resulting in widespread media attention and public health concern about the possible neurodegenerative effects of TBI. Based on preliminary neuropathological diagnostic published earlier this year [8], CTE has thus far only been found postmortem in individuals who were exposed to repetitive concussive or subconcussive head trauma during life [6].…”
Section: Resultsmentioning
confidence: 99%
“…This tauopathy called chronic traumatic encephalopathy (CTE) has since been identified postmortem in a small but growing number of individuals [4][5][6][7], resulting in widespread media attention and public health concern about the possible neurodegenerative effects of TBI. Based on preliminary neuropathological diagnostic published earlier this year [8], CTE has thus far only been found postmortem in individuals who were exposed to repetitive concussive or subconcussive head trauma during life [6]. However, the link between single TBI and dementia has been a topic of interest among researchers and clinicians for decades.…”
Section: Resultsmentioning
confidence: 99%
“…A recent reexamination of 1,721 specimens in a neurodegenerative brain bank found CTE changes in 21 of 66 former athletes with repetitive mild TBIs during sports participation ranging from high school to professional levels and no CTE changes among 198 controls or 33 cases with a history of remote single TBI. The majority (20/21) of the CTE cases were also diagnosed with at least 1 other neurodegenerative disorder (6 with AD, 4 with AD and DLB, 3 with ALS, 3 with DLB, 3 with FTLD-tau, and 1 with FTLD-FUS) (48).…”
Section: Discussionmentioning
confidence: 99%
“…57 However, the role of phosphorylated s in the genesis of the clinical syndrome is not yet clear. Bieniek et al 58 reported findings of a neuropathologic investigation of the brains of 66 individuals exposed to contact sports, such as football, drawn from a brain bank for neurodegenerative disorders. Twenty-one individuals met the pathologic criteria for CTE, compared with 0 individuals from the group of 198 individuals without contact-sport exposure.…”
Section: Long-range Cognitive Change and Neurodegenerative Diseasementioning
confidence: 99%